Molecular and Functional Characterization of a Wheat B2 Protein Imparting Adverse Temperature Tolerance and Influencing Plant Growth - Singh, Akanksha; Khurana, Paramjit (Frontiers in Plant Science, 2016)
Genomic attempts were undertaken to elucidate the plant developmental responses to heat stress, and to characterize the roles of B2 protein in mediating those responses. A wheat EST for B2 protein was identified which was cloned and characterized to assess its functional relevance causing plant growth and development during stress adaptation. Here, we show that wheat B2 protein is highly expressed in root and shoot tissues as well as in developing seed tissues under high temperature stress conditions. Morphological studies of transgenic Arabidopsis overexpressing gene encoding wheat B2 protein and Δb2 mutant plants were studied at major developmental stages. The stunted growth phenotype of mutant plants, together with hypocotyl and root elongation analysis of transgenic plants showed that B2 protein exhibits a crucial role in plant growth and development. Additional physiological analyses highlights the role of B2 protein in increased tolerance to heat and cold stresses by maintaining high chlorophyll content, strong activity of photosystem II and less membrane damage of overexpression transgenics as compared with the wild-type. Furthermore, the constitutive overexpression of TaB2 in Arabidopsis resulted in ABA hypersensitivity. Taken together, these studies suggest a novel perspectives of B2 protein in plant development and in mediating the thermal stress tolerance.